Variasi Stimulus dalam Pembelajaran Pelayanan Prima - Saripuddin User (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
The study on stimulus variation intended to create the learning process “prima service” could run well. In the sense that the participants of education and training could improve their knowledge of “prima service” materials after attending the training. The study was accomplished quantitatively by applying inferential statistics. The variation of stimulus consisted of three forms of variation, which were teaching style, media utilization and learning materials, and interaction patters and the participant activities had improved the knowledges of the participants on “prima service” materials. The results of statistical analysis obtained a calculated t value was greater than that of table t, which meant that the stimulus variations improved the knowledges of training participants on the “prima service” materials. On a scale of 0 to 100 values, the mean score before learning was 50.33 and increased to 87 after learning.